ANALISIS PERBANDINGAN SOLVABILITAS PADA KINERJA PERBANKAN SYARIAH DI INDONESIA BERDASARKAN INDIKATOR CAPITAL ADEQUACY RATIO (CAR) - Assafa, Syabila (Journal Economic Management and Business, 2025)
This research aims to compare the capital performance between Sharia Commercial Banks (BUS) and Sharia Business Units (UUS) in Indonesia during the period of 2019–2023 using the Capital Adequacy Ratio (CAR) indicator. In the context of national sharia economic growth, it is important to understand how institutional structure affects the strength and stability of sharia banking, particularly from the perspective of capital adequacy. This study employs a comparative quantitative approach utilizing secondary data sourced from the financial statements of sharia banks and official publications from the Financial Services Authority (OJK). The analysis is conducted using the Independent Samples T-Test to test the significance of the differences between the two types of banks. The results of this study are expected to contribute to regulators, industry practitioners, and academics in evaluating and formulating more effective and sustainable strategies for strengthening sharia banking in the future.